Defining the construct of synthetic androgen intoxication: An application of general brain arousal - Hildebrandt, T.; Heywood, A.; Wesley, D.; Schulz, K. (Frontiers in Psychology, 2018)
Synthetic androgens (i. e., anabolic-androgenic steroids) are the primary component to the majority of problematic appearance and performance enhancing drug (APED) use. Despite evidence that these substances are associated with increased risk for aggression, violence, body image disturbances, and polypharmacy and can develop a pattern of chronic use consistent with drug dependence, there are no formal definitions of androgen intoxication. Consequently, the purpose of this paper is to establish a testable theory of androgen intoxication. We present evidence and theorize that synthetic androgen intoxication can be defined by a pattern of poor self-regulation characterized by increased propensity for a range of behaviors (e.g., aggression, sex, drug seeking, exercise, etc.) via androgen mediated effects on general brain arousal. This theory posits that androgens reduce threshold for emotional reactivity, motor response, and alertness to sensory stimuli and disrupt inhibitory control over the behaviors associated with synthetic androgen use. These changes result from alteration to basic neurocircuitry that amplifies limbic activation and reduces top-down cortical control. The implications for this definition are to inform APED specific hypotheses about the behavioral and psychological effects of APED use and provide a basis for establishing clinical, legal, and public health guidelines to address the use and misuse of these substances.